PENGARUH TRANSPARANSI, AKUNTABILITAS DAN RESPONSIBILITAS TERHADAP KINERJA GURU PADA PONDOK PESANTREN MUQIMUS SUNNAH PALEMBANG - Siti Khodijah; Tien Yustini (Jurnal RATRI (Riset Akuntansi Tridinanti), 2022)
The purpose of this study was to determine the effect of transparency, accountability, and responsibility on teacher performance at the Muqimus Sunnah Islamic boarding school in Palembang partially or simultaneously. This research method uses descriptive and verification surveys, and field data collection uses questionnaires, interviews, and documentation techniques. This research is associative research, where in this study there are variables that are related and can influence other variables. The population of this study was teachers at the Muqimus Sunnah Islamic Boarding School in Palembang. Data processing using the SPSS analysis tool 25 The results of the research that there is an effect of transparency on teacher performance, accountability affects teacher performance, responsibility on teacher performance, as well as transparency, accountability, responsibility on teacher performance simultaneouslyKeywords: Transparency, Accountability, and Responsibility and Performance